Split-Hand Malformation in a 4-Year-Old Child - Girish Gulab Meshram; Kanwaljeet Singh Hura; Neeraj Kaur (Case Reports in Pediatrics)
Split-hand deformity is one of the milder manifestations of a congenital disorder called split-hand/split-foot malformation. We present a case of a 4-year-old child with split-hand malformation in his left hand since birth. A median cleft was present in the affected hand with absence of the 3rd and 4th digits, giving rise to a characteristic lobster-claw appearance. Functionality of the affected hand was modestly impaired. As none of the close family members of the patient had similar limb malformations, the deformity was postulated to arise most likely from a de novo mutation. The patient was discharged after the parents were provided with genetic counseling.